The problem of defining the subject of a criminal assault in the area of drug trafficking - Ігнатенко, Ю. М. (Problems of legality, 2013)
The article deals with problems of defining the subject of a criminal assault in illicit drugs, called attention to the criteria and reasons for inclusion of certain substances to the number of drugs.